2015
DOI: 10.4137/bcbcr.s23156
|View full text |Cite
|
Sign up to set email alerts
|

Altered Sirtuin 7 Expression is Associated with Early Stage Breast Cancer

Abstract: BACKGROUNDTo evaluate sirtuin-7 (SirT7) mRNA expression status in breast cancer patients with different metastatic stages and survey SirT7 mRNA expression status in eight different types of cancer.METHODSThe expression of SirT7 in the commercially available TissueScan qPCR Breast Cancer Disease cDNA arrays containing 16 normal, 23 Stage I, 36 IIA, 22 IIB, 8 IIIA, 23 IIIA, 6 IIIB, 13 IIIC, and 5 IV were evaluated by quantitative real-time polymerase chain reaction (qRT-PCR) assay. Similar analysis was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…On the other side, Sirt7 are consistently downregulated in tumorigenic cells compared to non-tumorigenic ones in mice 44 , and SIRT7 is negatively correlated with progression of human head and neck squamous cell carcinoma 45 . Interestingly, Aljada et al 46 showed that SIRT7 is significantly upregulated in early stage of breast cancers but gradually declined with tumor progression. Indeed, oncogenic transformation, tumor growth, and metastasis are phenotypically distinct and mechanistically different processes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, Sirt7 are consistently downregulated in tumorigenic cells compared to non-tumorigenic ones in mice 44 , and SIRT7 is negatively correlated with progression of human head and neck squamous cell carcinoma 45 . Interestingly, Aljada et al 46 showed that SIRT7 is significantly upregulated in early stage of breast cancers but gradually declined with tumor progression. Indeed, oncogenic transformation, tumor growth, and metastasis are phenotypically distinct and mechanistically different processes.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, sirtuins are considered to be tumor suppressors, but they may also act as tumor promoters particularly in advanced cancers [ 11 13 ]. Elevated levels of Sirt7 have been previously observed in several cancers including breast, liver, pancreas and colon [ 14 17 ]. SIRT7 is also associated with poor prognosis in gastric, lung, cervical and hepatocellular carcinoma [ 15 , 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ashraf et al (35) demonstrated that SIRT7 was significantly increased in breast cancer associated with node-positive breast cancer. Aljada et al (50) reported that high expression levels of SIRT7 were associated with early stage breast cancer (50). Furthermore, a high level of SIRT7 expression has been suggested as a predictor of adverse outcomes in breast cancer (36).…”
Section: Discussionmentioning
confidence: 99%